Application of Economic and Statistical Methods to Improve the Efficiency of Cinemas under Sanctions Conditions - O. G. Konyukova; A. N. Lukash (Статистика и экономика)
The relevance of the study involves the regular collection and accumulation of statistical data from commercial organizations engaged in activities in the field of film demonstration; their study and synthesis help to examine the work of business entities from different angles and draw appropriate conclusions. Using reliable information for a specific period of time, it is necessary to carry out calculations according to the necessary indexes for its further interpretation into scientific language. Without a detailed analysis of the current activities of the organizations under study, the risks of approving incorrect financial, investment, marketing, personnel and research policies towards economic recession and crisis increase, which can turn out negatively for both business owners and counterparties. In order to prevent such situations, it is necessary to constantly carry out calculations using economic and statistical methods and identify general trends in performance indexes.Purpose of the study. Study of the activities of LLC “Meridian” for the period 2018 – 2022 using statistical indexes and financial analysis parameters. Finding and interpreting each obtained value, describing the causes and consequences of external factors, as well as presenting a detailed forecast of the organization’s level of profitability for the coming years. Reflection of the obtained numerical values in tabular and graphical forms for the purpose of their use by internal and external stakeholders to make various kinds of decisions.Materials and methods. The research materials included regulatory documents, scientific publications of Russian and foreign authors, and accounting (financial) reporting data. The scientific article used the main research methods: monographic, comparative analysis, classification and generalization. The main methods of statistical and economic analysis were descriptive statistics, inferential statistics, regression analysis, time series analysis, etcResults. The practical application of statistical quantities and their significance is justified, as well as examples of their derivation using the Microsoft Excel package are demonstrated and Libre Office Tables (Calc) are considered as an alternative to this program. These calculations allow you to prevent negative financial situations, instantly respond to the changing internal and external environment of commercial activity and establish guidelines for increasing the efficiency of your activities.Conclusion. Based on the results of the conducted research on the text of the scientific article, recommendations are given to improve the efficiency of the cinema in question under sanctions conditions